Posterior Polar Hemispheric Choroidal Dystrophy - Shinji Makino (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
The term "posterior polar hemispheric choroidal dystrophy" was first used by Yannuzzi to describe the annular, hemispheric loss of retinal pigment epithelium and choriocapillaris [1]. Since then, there have been no further reports on this rare condition. Case Report A 71-year-old Japanese woman presented with gradual deterioration of the visual fields in both eyes for the past five years. She did not have a history of previous ocular or systemic illnesses. There was no family history of a similar disease. Best corrected visual acuity was 0.8 and 0.9 in her right and left eyes, respectively. The fundi showed bilateral symmetrical annular bands of depigmentation beginning at the lower part of the optic disc that passed along the course of the lower temporal vessels leading to increased visibility of the choroidal blood vessels (Figure 1). Bone spicule pigmentation of the retina was absent, and there was no evidence of narrowing of the retinal blood vessel. Fundus autofluorescence imaging (Heidelberg Retina Angiograph 2; Heidelberg Engineering, Heidelberg, Germany) showed clearly defined hypofluorescent areas that corresponded to the aforementioned lesions (Figure 2). Automated perimetry (Humphrey Field Analyzer model 750; Humphrey Instruments, Inc, Dublin, California) revealed an incomplete ring scotoma that corresponded to the above lesions (Figure 3).